Labor Adjustment Costs across Sectors and Regions - Cruz, Marcio; Milet, Emmanuel; Olarreaga, Marcelo (World Bank, Washington, DC, 2017)
This paper estimates the mobility costs of workers across sectors and regions in a large sample of developing countries. The paper develops a new methodology that uses cross-sectional data only. This is motivated by the fact that panel data typically are not available for most developing countries. The results suggest that, on average, sector mobility costs are higher than regional mobility costs. The costs of moving across sectors and regions are higher than the costs of moving across only sectors or only regions. In poorer countries, workers face higher mobility costs. The paper provides evidence suggesting that mobility costs, particularly across sectors, are partially driven by information assimetries and access to the Internet can mitigate these costs.